TECHNO ECONOMICS STUDY OF OCEAN THERMAL ENERGY CONVERSION AT OMBAI STRAIT, NUSA TENGGARA TIMUR - Yolanda
The need for electricity is increasing along with the progress of the times in the industrial sector and population growth, but it is actually accompanied by the depletion of the number of fossils that serve as the main source of electric power. Ocean Thermal Energy Conversion (OTEC) is present as an option for green renewable energy sources. Indonesia has great potential for OTEC development because it is located in the equatorial region, so the temperature at sea level is higher than in non-equatorial areas. One of the potential locations for the development of OTEC is the Ombai Strait, which is deep water and has a temperature difference between sea level and deep water in the range of 25?. Before being built and operated, it is necessary to conduct a feasibility analysis of the OTEC development. Therefore, the purpose of writing this Final Project is to determine the amount of power that needs to be generated by OTEC and determine the feasibility of building and operating OTEC within the next 30 years since operating in the Ombai Strait. Before the feasibility of the development and operation of OTEC is determined, it is necessary to carry out several calculation procedures, starting with the calculation of Capital Expenditure (CAPEX) and Operational Expenditure (OPEX) as expenditure data. The next step is to calculate the Levelized Cost of Energy (LCOE) or the comparison between spending during the time of use with the energy produced. Then, the amount of revenue or income from electricity sales is calculated based on the Decree of the Minister of Energy and Mineral Resources of the Republic of Indonesia concerning the BPP Generating PT. PLN (PERSERO) in 2020 and sales of desalinated water which is a by-product of OTEC. Finally, a financial feasibility analysis was carried out using the Net Present Value, Internal Rate of Return (IRR) and Benefit Cost Ratio (BCR) methods with an interest rate of 8.5% and an inflation rate of 1.95%. In this Final Project, there are three types of scenarios that will be reviewed in combination, namely scenarios based on the area of electricity supply, scenarios of projected electricity demand, and scenarios of projected electricity production capacity. The scenario based on the electricity distribution area is divided into two regions, namely Alor Regency and Timor Island. Electricity demand projection scenarios are divided into optimistic, moderate, and pessimistic scenarios. Then, the projected electricity production capacity scenario is divided into two, namely scenario 1 where the ability to produce electricity in an area is only produced by existing power plants in 2021 and scenario 2 where the ability to produce electricity in an area is in accordance with the planned RUPTL 2021 – 2030 document. The results obtained from the financial analysis are that OTEC is not feasible to be built in the Ombai Strait in all scenarios.